Evaluation of desmoglein 1 and desmoglein 3 autoantibodies in oral cancer: A pilot study - Pavan Kumar Yellarthi; Arvind Muthukrishnan; Raghurama Rao Gandikota; Y Sandhya Pavankumar; Divya Uppala (Wolters Kluwer Medknow Publications, 2023)
Background: Carcinogenesis is a complex multistep process involving alterations at the cellular level. Alteration in cell-to-cell adhesion of oral epithelium plays an important role in carcinogenesis and metastasis. The alterations in the role of desmosomal components due to autoantibodies to desmoglein 1 (DSG 1) and desmoglein 3 (DSG 3) may cause the detachment of the cells due to altered adhesiveness leading to initiation and metastasis. The exact role of autoantibodies in DSG 1 and 3 and their role in oral carcinogenesis remains unclear. Objectives: A pilot study was undertaken to evaluate autoantibodies to DSG 1 and 3 oral cancer (OC), Oral potentially malignant disorder (OPMDs) patients, and healthy controls. Materials and Methods: A total of 25 cases (15 OC, 5 OPMDs, and 5 healthy controls) were selected. Serum and tissue biopsies were taken and evaluated for autoantibodies to DSG 1 and 3 by enzyme-linked immunosorbent assay (ELISA) and was confirmed with direct immunofluorescence (DIF). Results: The DSG 1 and 3 values obtained were way below the positive value of 20 RU/ml for autoantibody levels for either DSG 1 or DSG 3 in serum. Direct immunofluorescence (DIF) of tissues also failed to demonstrate the presence of antibodies in all three groups. Conclusion: Though the results were not encouraging, they suggest a possible role of desmosomal components, DSG 1 and 3, in oral carcinogenesis and metastasis.